Non-breeding behaviour in the Brown Skua (Stercorarius antarcticus lonnbergi): insights from modelling moulting patterns and stable isotope analyses. (2nd January 2023) - Schultz, Hendrik; Battley, Phil F.; Bury, Sarah J.; Chang, Kevin; Ismar-Rebitz, Stefanie M. H.; Gaskett, Anne C.; Dennis, Todd E.; Hohnhold, Rebecca J.; Taylor, Graeme A.; Paul Scofield, R.; Rayner, Matt J.; Tennyson, Alan J. D.; et al.
ABSTRACT: Long-term changes in the life history and behaviour of seabirds during the non-breeding season can reflect shifts in environmental conditions. However, long-term marine studies are scarce, particularly on southern hemisphere seabirds. Here, we used moult scores from 86 Brown Skuas ( Stercorarius antarcticus lonnbergi ), a large predatory seabird breeding on the Chatham Islands, Aotearoa/New Zealand to model both the timing and duration of primary feather moult. In addition, we analysed stable isotope values (δ 13 C and δ 15 N) from 62 modern (2014–16) and ten museum tail feathers. These data provide insights into the non-breeding behaviour of Brown Skua. Interestingly, our results show that the primary feather moult occurred prior to birds departing the colony, starting on average on 2 January ± 5 days (SE). The average start of primary feather moult occurred five days prior to the end of breeding (7 January ± 10 days (SD)) and 42 days before the birds departed the colony (13 February ± 11 days (SD)). The average duration of primary feather moult was 189 ± 14 days (SE). Importantly, low δ 13 C values in four females suggested that tail feather moult might also occur while skuas are at the colony. There was no difference in tail feather δ 13 C and δ 15 N values between any pairwise comparison of modern and museum years. However, values of δ 15 N from tail feathers sampled in 2014 were different from those sampled in 2015 and 2016. This large annual variation in δ 15 N values from tail feathers over such a short period makes long-term comparisons difficult to interpret, particularly between years with low sample sizes. While the stable isotope analyses of tail feathers are informative, we recommend future studies of skuas sample the primary coverts rather than tail feathers.